Upaya Meningkatkan Kemampuan Membaca Al-Qur’an Dengan Tartil Melalui Penggunaan Metode Tilawati Pada Siswa Kelas IV Sekolah Dasar Islam Terpadu Irsyadul ‘Ibad - sulaiman, Mohammad Sulaiman Suryanto; Rifki Arif Nugraha; Yeni Sulaeman; Ade Farid Hasyim (KRAKATAU (Indonesian of Multidisciplinary Journals), 2023)
ABSTRACT  Mohammad Sulaiman Suryanto. 2023. Efforts to Improve the Ability to Read the Al-Qur'an with Tartil Through the Use of the Tilawati Method in Class IV (Four) Students at the Irsyadul 'Ibad Pandeglang Integrated Islamic Elementary School. Syekh Manshur Pandeglang Primary School Teacher Education and Science College (STKIP) Thesis. Supervisor I Yeni Sulaeman, M.Pd and supervisor II Ade Farid Hasyim, M.Pd. This research aims to improve the ability to read the Qur'an with Tartil through the use of the Tilawati method in Grade IV (Four) students at the Irsyadul 'Ibad Pandeglang Integrated Islamic Primary School for the 2023/2024 academic year by applying the Tilawati method. This research is action research whose implementation includes four stages, namely planning, action, observation and reflection, which consist of two cycles where each cycle is carried out in two meetings. The subjects in the research were 28 grade IV students at SDIT Irsyadul 'Ibad, Majasari District, Pandeglang Regency, consisting of 15 male students and 13 female students. Data collection instruments use observation sheets and tests. The data analysis technique used is qualitative descriptive analysis and quantitative descriptive analysis. The success of this research can be seen from student learning outcomes which have increased in cycle I and cycle II. The research results showed that there was an increase in student learning outcomes in their ability to read the Koran. The results of student learning completion in cycle I were that out of 28 students, there were 15 students or around 52% who had completed their studies and there were 13 students or around 48% who had not completed their studies. Meanwhile, in cycle II there was an increase in learning outcomes, namely there were 25 students or around 89% who had completed their studies and there were 3 students or around 11% who had not yet completed their studies with the average score of students experiencing an increase in cycles I and cycle II, namely from 69, 6 to 80.1. There were positive changes in attitudes and activities in students during the learning process according to the results of observations during classroom actions. Based on the results of this research, it can be concluded that the results of learning the ability to read the Koran in class IV SDIT Irsyadul 'Ibad Pandeglang through the use of the tilawati method have increased and received a positive response from students. Key words: reading ability, Al-Qur'an, tartil, tilawati method